Penyata peperiksaan komprehensif (compress): ke arah pengurusan peperiksaan yang efisien : Comprehensive examination slips (compress) towards efficient examination management / Jamal Othman ... [et al.] - Othman, Jamal; Wan Mohd Rosly, Wan Nur Shaziayani; Samsudin, Norshuhada; Syed Abdullah, Sharifah Sarimah; Mazeni, Noor Azizah Mazeni; Hamat, Muniroh; Zahari, Mohd Fahmi; Hasan, Suhaiza; Daud, Norziah; Md Kassim, Alina (Universiti Teknologi MARA, 2020)
Final Examination Slip is an official document allowing students to sit for an examination. Incomplete information on examination slip may cause the students to arrive late at the examination venue or even being absent from sitting the examination because mistakenly checking the examination schedule and venue, which is the worst case scenario. To overcome this problem, SDLC (System Development Life Cycle) methodology for the web based application development has been performed. Comprehensive Examination Slips or the acronym is Compress, allows students to generate and print their examination slips which this new slips will provide a complete information inclusive of dates, time, venues and the table numbers. Users have shown positive responds through the testing phase and the online feedback. Through the interviews with students and staffs, they are highly confident that the Compress has solved issues of incomplete information on examination slips and the examination management will be more efficient.